Reinforcer value moderates the effects of prenatal alcohol exposure on learning and reversal - Chandrasekaran, Jayapriya; Jacquez, Belkis; Wilson, Jennifer; Brigman, Jonathan L. (Frontiers in Neuroscience, 2023)
Introduction Fetal Alcohol Spectrum Disorders (FASD) are the leading cause of preventable developmental disability and are commonly characterized by alterations in executive function. Reversal learning tasks are reliable, cross-species methods for testing a frequently impaired aspect of executive control, behavioral flexibility. Pre-clinical studies commonly require the use of reinforcers to motivate animals to learn and perform the task. While there are several reinforcers available, the most commonly employed are solid (food pellets) and liquid (sweetened milk) rewards. Previous studies have examined the effects of different solid rewards or liquid dietary content on learning in instrumental responding and found that rodents on liquid reward with higher caloric content performed better with increased response and task acquisition rate. The influence of reinforcer type on reversal learning and how this interacts with developmental insults such as prenatal alcohol exposure (PAE) has not been explored. Methods We tested whether reinforcer type during learning or reversal would impact an established deficit in PAE mice. Results We found that all male and female mice on liquid reward, regardless of prenatal exposure were better motivated to learn task behaviors during pre-training. Consistent with previous findings, both male and female PAE mice and Saccharine control mice were able to learn the initial stimulus reward associations irrespective of the reinforcer type. During the initial reversal phase, male PAE mice that received pellet rewards exhibited maladaptive perseverative responding whereas male mice that received liquid rewards performed comparable to their control counterparts. Female PAE mice that received either reinforcer types did not exhibit any deficits on behavioral flexibility. Female saccharine control mice that received liquid, but not pellet, rewards showed increased perseverative responding during the early reversal phase. Discussion These data suggest that reinforcer type can have a major impact on motivation, and therefore performance, during reversal learning. Highly motivating rewards may mask behavioral deficits seen with more moderately sought rewards and gestational exposure to the non-caloric sweetener, saccharine, can impact behavior motivated by those reinforcers in a sex-dependent manner.